Male and Female Language in the Openings of Short Stories: A Transitivity Approach - Arthit Jittho,; Angkana Tongpoon-Patanasorn, (Journal of Mekong Societies, 2022)
This research project examined and compared the types of transitivity processes in the openings of English short stories used by male and female writers. The opening sections of twenty English modernist short stories written by male and female writers (ten of each) were used as the data source. The transitivity system in systemic functional grammar (SFG) was utilized for the data analysis, and the intra-rater reliability was strong standing at 99.19 percent. A total of 496 occurrences of transitivity process were found in the texts of both male and female writers. All types of the processes (i.e. material, mental, and relational) were found in the works of both genders. The material process was identified as the dominant process in this study (59.68 percent), while the relational process accounted for 21.37 percent of all the processes were found. The least common type was the mental process (18.95 percent). According to the results, both males and females employed the material processes as a tool to drive the flow of short stories forward in the opening sections. However, the second-most frequently used process employed by male writers was the relational process, whereas the female writers used the mental process. Wilcoxon U tests showed that there were no significant differences between the number of processes used in the introduction section between male and female writers, except the mental process. A clearer and better understanding of the differences between the language of male and female writers can be achieved through the transitivity approach, and the differing world views of male and female writers can be understood via the actual analysis of their language use.